Movie Palaces on Canadian Downtown Main Streets: Montreal, Toronto, and Vancouver - Moore, Paul (Urban History Review / Revue d'histoire urbaine, 2004)
The emergence of movie palaces is traced for St. Catherine Street in Montreal, Yonge Street in Toronto, and Granville Street in Vancouver. Beginning in 1896, film shows were included in a range of urban amusement places. When dedicated movie theatres opened by 1906, they were quickly built throughout the city before the downtown "theatre districts" became well defined. Not until about 1920 were first-run vaudeville-movie palaces at the top of a spatial hierarchy of urban film-going, lasting into the 1950s. After outlining the formation of movie palace film-going, the paper notes how the downtown theatres were next to each city's major department store. A theoretical analysis of how amusement and consumption make "being downtown" significant in everyday urban life follows. A review of the social uses of electric lighting and urban amusements finds that movie palace marquees become a symbol for the organization of downtown crowds and consumers into attentive mass audiences. A brief account of the decline of the movie palace, from the 1970s to 2000, concludes by reviewing the outcomes of replacement by multiplex theatres, demolition, or preservation.